2021
DOI: 10.1007/s11136-021-02808-2
|View full text |Cite
|
Sign up to set email alerts
|

Health state utilities associated with treatment process for oral and injectable GLP-1 receptor agonists for type 2 diabetes

Abstract: Purpose Previous research suggests that treatment process can have an influence on patient preference and health state utilities. This study examined preferences and estimated utilities for treatment processes of two daily oral treatment regimens and two weekly injectable regimens for treatment of type 2 diabetes (T2D). Methods Participants with T2D in the UK reported preferences and valued four health state vignettes in time trade-off utility interviews. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…The most frequently preferred treatment regimen was the LAI ART administered every two months. This result adds to previously reported findings suggesting that oral medication is not always preferred over injectable treatment options [ 30 ]. Current findings suggest that the LAI dose frequency of every two months is a welcome treatment option for many PLHIV, while other respondents were resistant to injections.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The most frequently preferred treatment regimen was the LAI ART administered every two months. This result adds to previously reported findings suggesting that oral medication is not always preferred over injectable treatment options [ 30 ]. Current findings suggest that the LAI dose frequency of every two months is a welcome treatment option for many PLHIV, while other respondents were resistant to injections.…”
Section: Discussionsupporting
confidence: 78%
“…Mean utility differences between health states were relatively small, which is common for treatment process utilities [ 29 , 30 , 47 , 48 ]. Still, small utility differences can have an impact on the outcome of an economic model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 47 Matza et al reported that nearly half of patients with T2DM prefer injectable to oral treatment if the former can be administered weekly instead of daily with oral treatment. 27 In oncology, Mansfield et al demonstrated that patients may prefer an IV schedule to oral treatment if the latter requires several pills a day or a complicated dosing schedule. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Following the VAS exercises, TTO exercises were conducted for each health state. Each TTO exercise comprised questions prompting the participants to select between x years in full health, and 20 years in the health state (rather than 10 years within the MVH protocol, as per published outcomes research in T2DM) [ 18 , 27 ]. At each step, if a participant selected full health, x was decreased, and if a participant selected the health state, x was increased.…”
Section: Methodsmentioning
confidence: 99%